1982
DOI: 10.1007/bf01953681
|View full text |Cite
|
Sign up to set email alerts
|

Histamine binding to H2 receptors stimulates phospholipid methylation in mast cells

Abstract: 966 divided in the same manner into 3 groups of 6 animals each: infected, heat-exposed and control. All animals were then injected i.p. with 1 ml of a 10% suspension of washed sheep erythrocytes, while those of the infected group were additionally injected with a sublethal dose of live Salmonella enteritidis (0.0002 mg bacterial dry weight) s. 6 h later, the animals of the heat-exposed group were placed at an ambient temperature of 37 0C, while the thermodes of the hypothalamus-cooled group were perfused with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The present data show that histamine stimulates PE methylation in rat brain synaptosomes, just as Tolone et al ( 1982) have previously shown in mast cells. Histamine ( 10 p M ) caused a rapid increase and decrease in phospholipid methylation in rat brain synaptosomes, with the peak in [3H]methyl incorporation being achieved at 45 s (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The present data show that histamine stimulates PE methylation in rat brain synaptosomes, just as Tolone et al ( 1982) have previously shown in mast cells. Histamine ( 10 p M ) caused a rapid increase and decrease in phospholipid methylation in rat brain synaptosomes, with the peak in [3H]methyl incorporation being achieved at 45 s (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…H 2 R couples to second messenger signaling pathways via the stimulatory G protein, Gα s (10), leading primarily to activation of adenylate cyclase and increased cAMP (1118). In addition, the activation of H 2 R leads to phospholipid methylation (19), an increase in the slow inward Ca 2+ current (20), stimulation of phospholipase C, intracellular Ca 2+ mobilization (21, 22), and inhibition of phospholipase A 2 activation (23). Furthermore, histamine binding to H 2 R leads to the activation of c‐Fos (8, 24, 25), c‐Jun (20), protein kinase C, and p70S6kinase (26).…”
mentioning
confidence: 99%
“…have proposed that N-methylation of membrane phospholipids plays an important role in the transduction of biochemical signals through membranes. Thus, PMTases in various tissues have been activated by such agents as dopamine in rat brain neurons (Leprohon et al, 1983), isoproterenol in rat reticulocyte ghosts (Hirata et al, 1979a), histamine in mast cells (Tolone et al, 1982), thyrotropin-releasing hormone in rat pituitary glands (Prasad et al, 1985), lectins in lymphocytes or mast cells (Hirata et al, 1979b), immunoglobulins in mast cells (Ishizaka et al,198 l), angiotensin or vasopressin in hepatocytes (Alemany et al,198 I), and glucagon in hepatocytes (Castano et al, 1980). Moreover, recent work in our laboratory has shown that histamine stimulates phospholipid methylation in synaptic membranes of rat brain acting on H2-receptors (Ozawa et al, 1987).…”
mentioning
confidence: 99%